THE FACTORS AFFECTING TENDENCY OF FRAUD IN GOVERNMENT SECTOR - Elinda Bayu Lestari; - Tarjo; - Prasteyono (Master of Accounting Universitas Trunojoyo Madura, 2017)
The purpose of this study is to explore perception of government officials in government agencies about the effects of morality of individuals, organizational culture, and leadership style on tendency of fraud. This study is a quantitative research using a survey which collected main data from the samples by using questionnaire. This research was analyzed with Multiple Linear Regression Analysis. The respondents of this research were the Subsection Head of Finance and Expenditure Treasurer. The findings indicate that morality of individuals has no significant effect on tendency of fraud, while organizational culture and leadership style have a significant negative effect on tendency of fraud.Tujuan penelitian ini adalah untuk menggali persepsi para pegawai pemerintah di instansi pemerintahan mengenai pengaruh moralitas individu, budaya organisasi, dan gaya kepemimpinan terhadap kecenderungan fraud. Penelitian ini menggunakan metode kuantitatif dengan cara survei yakni mengumpulkan data pokok dari suatu sampel dengan memakai instrumen kuesioner. Penelitian ini dianalisis dengan menggunakan Analisis Regresi Linier Berganda. Responden penelitian adalah kepada Kasubbag Keuangan dan Bendahara Pengeluaran. Hasil penelitian menunjukkan bahwa moralitas individu tidak berpengaruh signifikan terhadap kecenderungan fraud, sedangkan budaya organisasi dan gaya kepemimpinan berpengaruh negatif signifikan terhadap kecenderungan fraud.